When among crows - Roth, Veronica (Tor Publishing Group, 2024)
"Pain is Dymitr's calling. His family is one in a long line of hunters who sacrifice their souls to slay monsters. Now he's tasked with a deadly mission: find the legendary witch Baba Jaga. To reach her, Dymitr must ally with the ones he's sworn to kill. Pain is Ala's inheritance. A fear-eating zmora with little left to lose, Ala awaits death from the curse she carries. When Dymitr offers her a cure in exchange for her help, she has no choice but to agree. Together they must fight against time and the wrath of the Chicago underworld. But Dymitr's secrets--and his true motives--may be the thing that actually destroys them"--